The Pragmatics of Papal Rule: Books 3 and 4 of Bernard of Clairvaux's De consideratione - ANDERSON, JOHN (Cistercian studies quarterly, 2025)
The article focuses on how Bernard of Clairvaux's De consideratione, especially Books 3 and 4, develops a pragmatic vision of papal leadership shaped by historical crisis and personal observation. Topics include the shift from spiritual counsel to administrative guidance, Bernard's application of Augustinian frameworks to papal self-assessment and reform, and the influence of the Second Crusade and Bernard's close relationship with Pope Eugene III on his practical advice for governance.